Changes in Soil Micro-Structure for Natural Soft Clay under Accelerated Creep Condition. Issue 4 (18th May 2016) - Lei, Huayang; Lu, Haibin; Wang, Xuechao; Ren, Qian; Li, Bin
Abstract : The accelerated rheological properties of natural soft clay are the external power and predisposing factors of geological and geotechnical disasters. To determine the changes in soil micro-structure for natural soft clay under accelerated creep condition, a detailed study has been carried out using consolidated undrained tri-axial tests under static and cyclic loads, as well as experimental data from mercury intrusion porosimetry and a scanning electron microscope. In the tri-axial tests, creep of the soft clay would be accelerated under dynamic loads, the sample would be destroyed faster, and the strain-rate would increase clearly along with the increase of the vibration frequency. Based on a comparison of micro-structure behaviors between the intact sample and the test soil samples under static and dynamic loads in the creep condition, an interpretation of the changes in soil micro-structure for natural soft clay under an accelerated creep condition was proposed. The research indicated that the large pores of the soil sample gradually changed into small pores, the large particles continuously changed into tiny particles, and the pore distribution gradually became uniform under dynamic loads. It was found that the fractal dimension of the pores decreased with the increase of the vibration frequency. The test results not only showed that the accelerated creep characteristics depended on the vibration frequencies of the applied dynamic loads, but the accelerated creep was actually an unceasingly self-adjusting and reengineering process of the internal structure in soil under dynamic loads. In addition, these results revealed that there was a close relationship between the vibration frequencies and the micro-structure parameters.